2020
DOI: 10.3389/fimmu.2020.606878
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious Generation of Biparatopic Common Light Chain Antibodies via Chicken Immunization and Yeast Display Screening

Abstract: Bispecific (BsAb) and biparatopic (BpAb) antibodies emerged as promising formats for therapeutic biologics exhibiting tailor-made functional properties. Over recent years, chicken-derived antibodies have gained traction for diagnostic and therapeutic applications due to their broad epitope coverage and convenience of library generation. Here we report the first generation of a biparatopic common light chain (cLC) chicken-derived antibody by an epitope binning-based screening approach using yeast surface displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…Biolayer interferometric measurements revealed no epitope drift, as dFEB4-1 targeted the same epitope as the parental FEB4 mAb, exhibiting an overlapping epitope with matuzumab, but not with cetuximab (Supplementary Figure 4). These results are in accordance with previous binning experiments performed with the parental antibody variant (54). Additionally, BLI measurements showed that EGF interferes with the ability of dFEB4-1 to bind EGFR (Figure 3A), comparable to the parental molecule or cetuximab (54).…”
Section: Anti-egfr Fab: Affinity Maturation By Light Chain Shufflingsupporting
confidence: 92%
See 3 more Smart Citations
“…Biolayer interferometric measurements revealed no epitope drift, as dFEB4-1 targeted the same epitope as the parental FEB4 mAb, exhibiting an overlapping epitope with matuzumab, but not with cetuximab (Supplementary Figure 4). These results are in accordance with previous binning experiments performed with the parental antibody variant (54). Additionally, BLI measurements showed that EGF interferes with the ability of dFEB4-1 to bind EGFR (Figure 3A), comparable to the parental molecule or cetuximab (54).…”
Section: Anti-egfr Fab: Affinity Maturation By Light Chain Shufflingsupporting
confidence: 92%
“…Recently, we isolated a chicken-derived EGFR-specific antibody termed FEB4 from an immune library comprising a restricted light chain diversity. The respective antibody showed affinity in the lower-double-digit nanomolar range, targeted a conformational epitope on EGFR domain III, exhibited an overlapping binding site with matuzumab, and inhibited EGF binding to its receptor (54). Due to its ability to block EGF binding to its receptor, as well as targeting a proximal binding site to the intensively investigated matuzumab epitope, we chose FEB4 as a starting molecule.…”
Section: Anti-egfr Fab: Affinity Maturation By Light Chain Shufflingmentioning
confidence: 99%
See 2 more Smart Citations
“…Assembly of the MD expression constructs was conducted with 75 ng destination vector and equimolar amounts of the respective fragments, 20 U BbsI-HF, 10 U Esp3I, and 200 U T4-DNA ligase (NEB, Frankfurt, Germany) for 30 cycles (1 min; 16 • C; 37 • C). For the reference constructs, VH and VL genes were amplified incorporating SapI restriction sites and then inserted into a pTT5-derived vector utilizing CH1-CH2-CH3 or κ/λ entry vectors using GGC as described before [24,25]. PCR reactions were performed utilizing Q5 polymerase (NEB) according to the manufacturer's protocol and purified using the Wizard SV Gel and PCR Clean-up System (Promega, Walldorf, Germany).…”
Section: Plasmids and Cloning Of Constructsmentioning
confidence: 99%